MPM‐driven dynamic desiccation cracking and curling in unsaturated soils - Tu, Zaili; Peng, Chen; Li, Chen; Wang, Chenhui; Liu, Long; Wang, Changbo; Qin, Hong (Computer animation and virtual worlds, 2023)
Desiccation cracking of soil‐like materials is a common phenomenon in natural dry environment, however, it remains a challenge to model and simulate complicated multi‐physical processes inside the porous structure. With the goal of tracking such physical evolution accurately, we propose an MPM based method to simulate volumetric shrinkage and crack during moisture diffusion. At the physical level, we introduce Richards equations to evolve the dynamic moisture field to model evaporation and diffusion in unsaturated soils, with which a elastoplastic model is established to simulate strength changes and volumetric shrinkage via a novel saturation‐based hardening strategy during plastic treatment. At the algorithmic level, we develop an MPM‐fashion numerical solver for the proposed physical model and achieve stable yet efficient simulation towards delicate deformation and fracture. At the geometric level, we propose a correlating stretching criteria and a saturation‐aware extrapolation scheme to extend existing surface reconstruction for MPM, producing visual compelling soil appearance. Finally, we manifest realistic simulation results based on the proposed method with several challenging scenarios, which demonstrates usability and efficiency of our method. This article presents a method for simulating desiccation cracking in unsaturated soils. The method includes an MPM‐based solver that tracks the dynamic strength of soils and pore water movements, as well as an improved surfacing technique for better crack mesh capture. The results demonstrate the method's effectiveness in capturing realistic details of shrinkage, cracking, and curling effects in soils.